THE IMPLEMENTATION OF THE MONTESSORI METHOD IN BUILDING LEARNING MOTIVATION IN LOW ELEMENTARY AT BRAINY BUNCH INTERNATIONAL ISLAMIC MONTESSORI SCHOOL, MALAYSIA - Azrial Syahrur Ramadahn (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
Montessori method for childhood especially low elementary is needed where the method teaches students to become independent and highly motivated individuals. This study aims to analyze the implementation of the Montessori method at the Brainy Bunch International Islamic Montessori School in building self-reliance and motivation in students. This study uses a case study method in qualitative research with descriptive analysis. The determination of participants in this study was carried out using a purposive sampling technique in which the participants included school principals, kindergarten managers, and teachers. The secondary data sources in this study are reference books and journals related to the Montessori method and learning motivation. Data collection techniques using observation techniques, interviews, and documentation. Checking the validity of the data using triangulation. This research shows that the application of the Montessori method in building learning motivation in young children is well done which includes lesson planning, implementation, and learning evaluation. The independent learning contained in the Montessori method has an impact on building students' learning motivation which can be seen from the ability of students to learn independently.